ダイ5ジ ナンキョク チイキ カンソクタイ ウチュウセン ブモン センジョウ カンソク ホウコク - 牧野, 忠男; マキノ, タダオ; MAKINO, Tadao (国立極地研究所, 1962)
P(論文) The fourth cosmic ray latitude survey in nucleonic and meson components was carried out on M/S "SOYA" during the full voyage to and from Antarctica. The observation room was the same as in the preceding survey. The intensity of the nucleonic component was measured by the same apparatus as before, while the intensity of meson component was observed by a Neher-type ionization chamber. The obtained data were corrected for barometric pressure effect and for the primary cosmic ray intensity variation deduced from the nucleonic component at sea level. The data of meson component were also corrected for atmospheric temperature effect, as well as for the above two effects. Results: 1. Obtained latitude factors were 55% for nucleonic component and 11% for meson component, respectively. 2. Knee of the latitude curves was found to be at geomagnetic latitude 35°S, and geographic longitude 20°E in both components. 3. Minimum intensity point was found to occur at geomagnetic latitude 5°S, and geographic longitude 107°E. 4. Longitude effects between 87°E-109°E and 18°E-34°E were -1.1%/deg. and -2.3%/deg., respectively in nucleonic component. The results 2, 3 and 4 were identical with those of the preceding three surveys. That is to say, they do not correspond to the relative sun spot numbers. According to the previous report the latitude factor follows the relative sun spot numbers inversely with a half year delay. Comparing with the preceding three surveys, the present result (Result 1) would be expected to become larger than 60%. However, the present result showed 55%. Also meson component in the first survey got latitude factor of 12%, so in the present survey it was expected to becomelarger than 12%, but the present result showed 11%. Therefore our result is not consistent with the preceding report. Reexamining the preceding three surveys, we have got the results shown in Fig. 2. These results mean that latitude factor rather follows the relative sun spot numbers. The results will be checked again with our next ...